Large scale implementation of higher order thinking (HOT) in civic education: The interplay of policy, politics, pedagogical leadership and detailed pedagogical planning. (September 2016) - Zohar, Anat; Cohen, Adar
Highlights: The paper examines two decades of implementing HOT in civic studies in Israel. A policy advocating HOT in civic studies had little impact for more than 10 years causing unexpected consequences. Implementation demonstrates the development of instructional leadership and a blend of "top down" and "bottom up" processes. Deep knowledge about teaching HOT is necessary for large scale implementation. Abstract: Educational policy documents from around the globe currently highlight the goal of teaching higher order thinking (HOT). Yet, most classrooms worldwide are still predominately characterized by a pedagogy of knowledge transmission, focusing on lower-order cognitive levels. This discrepancy points to the need to study issues of large scale implementation of HOT. The goal of this paper is to address this issue by examining two decades of implementing HOT in civic education in Israel, adopting a dual approach: first, the paper provides a historical analysis of relevant policies and political transformations, showing what happens to a policy decision to foster HOT over the years. The analysis shows that the way from a policy paper to what actually had taken place in classrooms is long and bumpy. The policy did cause several practical changes, but for more than 10 years, impacts were slim, sometimes causing unexpected (and undesirable) consequences. Then, the paper zooms-in on one specific period in which more elaborate implementation efforts took place. Significant hallmarks of the process were an emphasis on developing instructional leadership, detailed pedagogical planning, a blend of tight "top down" processes with "bottom up" processes characterized by growing freedom and autonomy, and modelling the culture of thinking.